Slavica Biblioteconomica - Mazzitelli, Gabriele (Biblioteca di Studi Slavistici, 2007)
Despite having been written at different times and being characterised by a great variety of subject and a multiplicity of approach, the essays of Gabriele Mazzitelli gathered here all appear to have been triggered by a precise and organic project of exploration. In fact what pervades them all is his love of the book, seen on the one hand as an unrepeatable and magnificent object produced by individual genius and the cultural legacy, and on the other as a medium of knowledge, an intellectual and spiritual bond. The book beloved of Mazzitelli is that of the rich and variegated Slav cultural tradition. It is the Russian book first and foremost, but not only, and not in the abstract dimension of the erudite bibliographic citation, but in the lively, shifting and at times perishable dimension of the library, seen as a living site of encounter and study. The life of the Slav book in Italy depends upon its full accessibility and its complete valorisation. The studies in this volume represent a crucial passage towards the full realisation of this goal.